Kinematics Analysis of the Leg-wheel Walking System of Engineering Machinery with Variable Structure - Luo Jinliang; Wen Qun; He Jialai (Jixie chuandong)
The kinematics model of walking system with variable structure of engineering machinery is established.The forward kinematics analysis and inverse kinematics analysis of right front leg is conducted,the explicit formulation of the position,velocity and acceleration at the end of right front leg is obtained.With the inverse kinematics analysis,the revolute angle of each joint in the right front leg is got with given end location of right front leg.Based on the kinematics analysis,the working space of the right front leg is solved through Monte Carlo algorithm by Matlab.